Analysis of Islamic Economic Principles in Financial Technology in Indonesian Islamic Banking - Eny Latifah (Involvement International Journal of Business, 2024)
The purpose of this research in to provide an overview of the implementation of financial technology in the mobile banking system owned by Bank Muamalat Indonesia and what Islamic economic principles are used in its implementation. The research method uses a qualitative with type of case study  at the Lamongan sub-branch office, East Java, Indonesia. The result of the research is the implementation of financial technology in Islamic Banking namely Bank Muamalat Indonesia by features. The principle of Islamic economics applied is not to make transactions that contain riba, gharar, maysir, tadlis, riswah and isyraf in financial technology services with Muamalat DIN features found in mobile banking.